Unravelling Indigenous Pedagogy: Tracing Dances and Songs of Dangaura Tharus (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This paper attempts to explore the underpinning pedagogy in Tharu culture – songs and dances of Dangaura Tharus- performed in various feast and festivals. Along with this, my study focused on examining the connections of the Tharus' pedagogies with that of the formal and non-formal schools. I employed interpretivism as a research paradigm and ethnography as a research design which includes focus group discussion, observation and interview with Chairperson of Guruwas (Tharu Priests), 4 Morihyas (leader of Singer), 4 Barghars (village Chief) and 4 Tharu social elites of the Kailali district of the Far western province as methodology. I interpreted the pedagogy embedded in Tharu dances and songs; interconnected to western learning theories, Gardner's multiple intelligence theory and Aboriginal pedagogy. I theorize the objectives, contents, teaching methods, evaluation process and revision process embedded in Tharu songs and dances. I concluded that each culture has its own pedagogical process and pedagogy embedded in any culture can be applied for learning in formal as well as non-formal education systems. It is where I expect that the present study is of substantial importance for the teachers, educational planners, policy makers of formal education. यस अध्ययनले डंगौरा थारूहरूले विभिन्न चाडपर्वहरूमा प्रस्तुत गर्ने नृत्य तथा गीतहरुमा निहित शिक्षण कलाको अनुसन्धान गर्ने प्रयास गरेको छ । यसको साथै यो अध्ययन थारूहरूको शिक्षण कलाको सम्बन्ध औपचारिक तथा अनौपचारिक विद्यालयसँग कस्तो छ भनी लेखाजोखामा केन्द्रित छ । यो अनुसन्धान अन्तरक्रियात्मक अनुसन्धान प्यारडाइम तथा इथ्नोग्राफी ढाँचामा रहेर गरिएको छ जसमा मैले सुदूरपश्चिम प्रदेशको कैलाली जिल्लाको गुरुवाहरु (थारू पुरोहितहरु)को अध्यक्ष, ४ जना मोरिह्याहरु (अगुवा गायक), ४जना बरघरहरु (गाउँ प्रमुख) तथा ४जना थारू अगुवाहरुसँग छलफल, अवलोकन तथा अन्तर्वार्ता लिएको छु । यसमा थारू नृत्य तथा गीतहरुमा निहित शिक्षण कलाहरु पाश्चात्य सिकाइका सिद्धान्तहरु, गार्डनरको बहुबौद्धिकताको सिद्धान्त तथा रैथाने शिक्षणकलासँग अन्तर सम्बन्धित रहेको कुरालाई व्याख्या गरिएको छ । थारू नृत्य तथा गीतहरुमा निहित उद्देश्य, शिक्षण विधि, मूल्यांकन प्रक्रिया र परिमार्जन प्रक्रियालाई सैद्धान्तिकरण गरेको छु । सबै संस्कृतिका फरक फरक शिक्षणकला हुन्छन् र तिनिहरुलाई औपचारिक तथा अनौपचारिक शिक्षण सिकाइमा प्रयोग गर्न सकिन्छ भन्नु मेरो निष्कर्ष हो । यो अन्वेषण शिक्षक, शैक्षिक योजनकारहरु, औपचारिक शिक्षाका निति निर्माताहरुका लागि महत्वपूर्ण हुने अपेक्षा छ ।